Entre o extrativismo e a catação: utilização das sementes de andiroba (Carapa Guianensis Aublet.) no Município de Marapanim (Pará, Brasil) - FURTADO, Diego Corrêa (Universidade Federal do Pará, 2021)
Andiroba (Carapa guianensis Aublet) is a plant species typical of semi-flooded or non-flooded forests, but, in Pará state (Brazil), its seeds disperse through water courses, reaching beaches. From such fact, the present study issued to investigate how the productive and symbolic appropriation of this species is performed by human populations who live in the mentioned beaches, also comparing the collected data with the information described in the scientific literature, which, so far, has been concentrating its efforts on the forest context. Field research was at Marapanim municipality, and as study method, it was chosen the case study, associated to participatory observation, interviews with semi-structured scripts, guided visits and thematic debates. The study concluded that the extraction of the andiroba seeds oil in Marapanim is based on technical knowledge and symbolic constructions introduced by people came from areas where andiroba tree is typical. Such work increases familiar income during the months that follow the species period, but the absence of andiroba trees at the local beaches brings doubts on the way how the research subjects express their identification as extractivists.